Telemedicine for sustainable postoperative follow-up: a prospective pilot study evaluating the hybrid life-cycle assessment approach to carbon footprint analysis - Lathan, Ross; Hitchman, Louise; Walshaw, Josephine; Ravindhran, Bharadhwaj; Carradice, Daniel; Smith, George; Chetter, Ian; Yiasemidou, Marina (Frontiers in Surgery, 2024)
Introduction Surgical site infections (SSI) are the most common healthcare-associated infections; however, access to healthcare services, lack of patient awareness of signs, and inadequate wound surveillance can limit timely diagnosis. Telemedicine as a method for remote postoperative follow-up has been shown to improve healthcare efficiency without compromising clinical outcomes. Furthermore, telemedicine would reduce the carbon footprint of the National Health Service (NHS) through minimising patient travel, a significant contributor of carbon dioxide equivalent (CO2e) emissions. Adopting innovative approaches, such as telemedicine, could aid in the NHS Net-Zero target by 2045. This study aimed to provide a comprehensive analysis of the feasibility and sustainability of telemedicine postoperative follow-up for remote diagnosis of SSI. Methods Patients who underwent a lower limb vascular procedure were reviewed remotely at 30 days following the surgery, with a combined outcome measure (photographs and Bluebelle Wound Healing Questionnaire). A hybrid life-cycle assessment approach to carbon footprint analysis was used. The kilograms of carbon dioxide equivalent (kgCO2e) associated with remote methods were mapped prospectively. A simple outpatient clinic review, i.e., no further investigations or management required, was modelled for comparison. The Department of Environment, Food, and Rural Affairs (DEFRA) conversion factors plus healthcare specific sources were used to ascertain kgCO2e. Patient postcodes were applied to conversion factors based upon mode of travel to calculate kgCO2e for patient travel. Total and median (interquartile range) carbon emissions saved were presented for both patients with and without SSI. Results Altogether 31 patients (M:F 2.4, ±11.7 years) were included. The median return distance for patient travel was 42.5 (7.2–58.7) km. Median reduction in emissions using remote follow-up was 41.2 (24.5–80.3) kgCO2e per patient (P < 0.001). The carbon offsetting value of remote follow-up is planting one tree for every 6.9 patients. Total carbon footprint of face-to-face follow-up was 2,895.3 kgCO2e, compared with 1,301.3 kgCO2e when using a remote-first approach (P < 0.001). Carbon emissions due to participants without SSI were 700.2 kgCO2e by the clinical method and 28.8 kgCO2e from the remote follow-up. Discussion This model shows that the hybrid life-cycle assessment approach is achievable and reproducible. Implementation of an asynchronous digital follow-up model is effective in substantially reducing the carbon footprint of a tertiary vascular surgical centre. Further work is needed to corroborate these findings on a larger scale, quantify the impact of telemedicine on patient's quality of life, and incorporate kgCO2e into the cost analysis of potential SSI monitoring strategies.